The Effect of Net Income, Equity, Cash Dividend, Average Price and Volume to Corporate Market Capitalization Stocks in LQ45 Index of Indonesia Stock Exchange Period 2008 – 2018 - Komang Indrayana; Djabir Hamzah; Andi Aswan (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2020)
One of the three aspects that influences the success of the stock investment, uses to understand the various data and information available in the financial market for investor’s decisions. There is two analysis, fundamental and technical. The fundamental analysis applies Net Income, Equity, and Cash Dividend, while technical analysis applies Average Prices and Volume. All of these variables will be examined their effect on the Corporate Market Capitalization. Samples are stocks that have been or currently in the LQ45 index for the period 2008 - 2018. This research utilized path analysis for the analytical method, on the SPSS program. All variables need to be transformed to get through the normality test. It transformed again with the Cochrane Orcutt method because of autocorrelation. The method applied outlier data tests, multicollinearity, the Sobel test without heteroscedasticity. The results show that Net Income and Equity simultaneously or individually, have a positive and significant effect on Cash Dividend, which is a mediating variable to the Corporate Market Capitalization. Furthermore, Net Income, Equity, Cash Dividend, Average Price, and Volume simultaneously or individually, have a positive and significant effect on the Corporate Market Capitalization.